Electron irradiation of the material samples of new generation nuclear reactors in the supercritical water convection loop - Bakai, A.S.; Boriskin, V.N.; Bratchenko, M.I.; Biller, E.Z.; Bytenko, P.A.; Bocharov, V.A.; Vereshchaka, V.N.; Dovbnya, A.N.; Duldya, S.V.; Gorenko, Yu.V.; Kovalev, G.G.; Momot, V.A.; et al. (Вопросы атомной науки и техники, 2013)
The design of the Supercritical Water Convection Loop with an irradiation chamber is described [1]. The plant makes possible to carry out simulation corrosion tests of potential structural materials for Generation IV reactors with the Supercritical Water-Cooling under irradiation. Specimens in water flow were irradiated in situ by the 10 MeV/10 kW electron beam of the LAE-10 linear accelerator. The high power relativistic electron-gamma irradiation delivers the absorbed doses sufficient for activation of corrosion and oxidation of material-coolant interfaces. The first results of the electron irradiation of Zr and Inconel 690 samples during 500 hours are gave.